The Impact of System Quality, Information Quality, and Service Quality of Rail Ticketing System (RTS) on Customer Satisfaction of PT. Kereta Api Indonesia - Waruwu, Ovi Selviani; Andini, Putri; Waruwu, Selvia Sari; Zebua , Fitriani; Della Crisanta, Della Crisanta; Butar Butar, Dwi Fany Fransiska Dewi (Global Insights in Management and Economic Research, 2025)
Purpose of the study: This research aims to examine the influence of system quality, information quality, and service quality of the Rail Ticketing System (RTS) on customer satisfaction among PT. Kereta Api Indonesia passengers in Medan City. Materials and methods: A quantitative cross-sectional study was conducted with 385 passengers of PT. Kereta Api Indonesia in Medan City, Indonesia, selected through purposive sampling. Data were collected using structured questionnaires measuring system quality, information quality, service quality, and customer satisfaction. Statistical analyses included descriptive statistics, Pearson correlation analysis, and path regression analysis using SPSS version 28. Results: The findings revealed that system quality (β = 0.324, p < 0.001), information quality (β = 0.287, p < 0.001), and service quality (β = 0.391, p < 0.001) significantly and positively influenced customer satisfaction. The model explained 68.4% of the variance in customer satisfaction (R² = 0.684). Service quality demonstrated the strongest impact on customer satisfaction, followed by system quality and information quality. Conclusions: All three quality dimensions of RTS significantly contribute to customer satisfaction, with service quality being the most influential factor. These findings suggest that PT. Kereta Api Indonesia should prioritize service quality improvements while maintaining high standards in system and information quality to enhance overall customer satisfaction.